2021
DOI: 10.1007/s00265-021-03058-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reproductive state on activity budget, feeding behavior, and urinary C-peptide levels in wild female Assamese macaques

Abstract: The source of maternal energy supporting reproduction (i.e., stored or incoming) is an important factor determining different breeding strategies (capital, income or mixed) in female mammals. Key periods of energy storage and allocation might induce behavioral and physiological shifts in females, and investigating their distribution throughout reproduction helps in determining vulnerable phases shaping female reproductive success. Here, we examined the effects of reproductive state on activity budget, feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 121 publications
1
23
0
Order By: Relevance
“…Additionally, we found that the only lactating female (Rajaja) spent most of the time resting. This is in line with previous studies that showed lactating females rest more at the cost of foraging and feeding as an energy-saving strategy [ 15 , 85 ]. However, our study only contained a single lactating female, and removing her from the sample did not significantly affect the time-activity budget, therefore conclusions should be taken with caution.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, we found that the only lactating female (Rajaja) spent most of the time resting. This is in line with previous studies that showed lactating females rest more at the cost of foraging and feeding as an energy-saving strategy [ 15 , 85 ]. However, our study only contained a single lactating female, and removing her from the sample did not significantly affect the time-activity budget, therefore conclusions should be taken with caution.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we examined the individual variation in behavioural states using goodness of fit chi-square tests. Analyses were also run without the lactating female in the sample since lactation may impact the time-activity budget, favouring resting over foraging as an energy-saving strategy [ 15 ]. We assessed whether potential differences in the time-activity budget were due to individual variation rather than differences in reproductive state.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and the habitat comprises mainly hill and dry evergreen forest (Borries et al 2002). The study population is frugivorous with the main part of their plant diet comprising fruit, pulp, and seeds, and a considerable part of their feeding time budget devoted to slow and low intake foraging for animal matter (Schülke et al 2011;Heesen et al 2013;Touitou et al 2021a). Individuals measured for this study lived in four neighboring social groups with overlapping home-ranges.…”
Section: Study Population and Demographymentioning
confidence: 99%
“…Reproduction was seasonal with 79% of 201 births recorded between 2006 and 2019 occurring in the 3 months from April through June (Touitou et al 2021a;unpubl. data).…”
Section: Study Population and Demographymentioning
confidence: 99%